Diagnosis and management of neutropenia in children: The approach of the Study Group on Neutropenia and Marrow Failure Syndromes of the Pediatric Italian Hemato‐Oncology Association (Associazione Italiana Emato‐Oncologia Pediatrica ‐ AIEOP). Issue 6 (6th March 2022) - Fioredda, Francesca; Onofrillo, Daniela; Farruggia, Piero; Barone, Angelica; Veltroni, Marinella; Notarangelo, Lucia Dora; Menna, Giuseppe; Russo, Giovanna; Martire, Baldassarre; Finocchi, Andrea; Verzegnassi, Federico; Bonanomi, Sonia; et al.
Abstract: Neutropenia refers to a group of diseases characterized by a reduction in neutrophil levels below the recommended age threshold. The present study aimed to review the diagnosis and management of neutropenia, including a diagnostic toolkit and candidate underlying genes. This study also aimed to review the progress toward the definition of autoimmune and idiopathic neutropenia rising in infancy or in late childhood but without remission, and provide suggestions for efficient diagnostics, including indications for the bone marrow and genetic testing. The management and treatment protocols for common and unique presentations are also reviewed, providing evidence tailored to a single patient.